1999
DOI: 10.1351/pac199971101889
|View full text |Cite
|
Sign up to set email alerts
|

Application of transferred arcs to the production of nanoparticles

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Large scale synthesis of nanomaterials of varieties of metals, metal oxides and nitrides using thermal arc plasma assisted gas phase synthesis, has gained importance in the recent years [5].…”
Section: Introductionmentioning
confidence: 99%
“…Large scale synthesis of nanomaterials of varieties of metals, metal oxides and nitrides using thermal arc plasma assisted gas phase synthesis, has gained importance in the recent years [5].…”
Section: Introductionmentioning
confidence: 99%
“…This method does not require costly equipment in its setup, leading to remarkably lower investment costs compared with the other well-known methods. Moreover, it is very simple and offers the advantage of fabricating various nanostructures by varying the system configuration and deposition parameters [25][26][27]. The plasma evaporator may be scaled up over a broad range of powers by increasing the current (100-2000 A) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is very simple and offers the advantage of fabricating various nanostructures by varying the system configuration and deposition parameters [25][26][27]. The plasma evaporator may be scaled up over a broad range of powers by increasing the current (100-2000 A) [25]. Many researchers have employed the arc discharge method [25][26][27][28], yet no report has appeared addressing the current and media effect on Al Nps arc discharge synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The SEM images show spherical particles, however it was observed that with an increase in H 2 concentration, the particle size was increased. This is attributed to the difference in vaporization rate due to the hydrogen addition in the arc, leading to a higher vapour concentration and resulting in larger diameters of the nanoparticles [42,43] The 2D AFM images (Figure 6) of the NAP prepared under different plasma compositions also confirm the increase in the particle size. However, the particles are < 200 nm at 20% H 2 dilution.…”
Section: Nap Prepared At Different H 2 Dilutionsmentioning
confidence: 99%